2013
DOI: 10.3109/09638288.2013.782357
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions of people with multiple sclerosis about the NHS provision of physiotherapy services

Abstract: This study has revealed that NHS physiotherapy provision is not meeting the needs of PwMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Questionnaire surveys have given some indication of progress in satisfaction with neurological services but also highlight concerns about delayed diagnosis [12,52], referral and access to neurological specialists [13,[60][61][62], cognitive and emotional support [61][62][63][64], a fragmented pathway, and clarity about the processes for monitoring local community rehabilitation and support services [12,13,52]. Discrepancies have been identified between peoples' experiences and service commissioners' perceptions of how community services are being delivered [12,45,65].…”
Section: Research Into Patient Experiencesmentioning
confidence: 99%
“…Questionnaire surveys have given some indication of progress in satisfaction with neurological services but also highlight concerns about delayed diagnosis [12,52], referral and access to neurological specialists [13,[60][61][62], cognitive and emotional support [61][62][63][64], a fragmented pathway, and clarity about the processes for monitoring local community rehabilitation and support services [12,13,52]. Discrepancies have been identified between peoples' experiences and service commissioners' perceptions of how community services are being delivered [12,45,65].…”
Section: Research Into Patient Experiencesmentioning
confidence: 99%
“…However, poor patient satisfaction with access to multiple sclerosis physiotherapy services has been reported in several areas of the United Kingdom (Edmonds et al, 2007;MacLurg et al, 2005;Markwick et al, 2014). In the Republic of Ireland, access to physiotherapy is reportedly lower in those from rural areas and in people with progressive multiple sclerosis compared to people with relapsing remitting multiple sclerosis (Lonergan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…'s study on the physiotherapy services provided by the British National Health System showed that the patients complained about the long wait. [ 48 ] In Brandon's study, patients were dissatisfied with the long waiting list. [ 44 ]…”
Section: Discussionmentioning
confidence: 99%